Value Predictors of Older Adolescents' Growing-up in the Context of Their Professional Self-Determination: A Case Study of Cadets of the Suvorov Military School of the Ministry of Internal Affairs of Russia - Svetlana A. Bezgodova; Alina V. Kulinchenko; Anastasia V. Miklyaeva; Valentin A. Shapoval (Peoples' Friendship University of Russia (RUDN University), 2021)
Against the background of social changes in the last decade, the increasing priority of the role of a child in relation to the role of an adult, modern adolescents are faced with a choice of growing-up strategies, which is accompanied by an internal conflict of this process, a contradiction between the laws of development, including social and modern cultural imperatives. This urgent problem is in the focus of the presented research. The process of modern Russian adolescents growing-up in the context of their professional self-determination is analyzed. Professional self-determination is considered as a factor of positive growing-up acceptance due to certain value orientations. It is assumed that the choice of a future profession made by adolescents (i.e., their professional self-determination) increases their self-assessment of adulthood, and value orientations can act as its predictors as determining the meaning of growing up for them. The study involved 302 male teenagers aged 14-17 years, including: 148 cadets of the Suvorov School of the Ministry of Internal Affairs of Russia and 154 students of secondary schools. The study used the questionnaire method, modified Dembo - Rubinstein Self-Assessment Methods and Schwartz Value Survey. Statistical processing was based on a comparative ( F -tests and the Mann -Whitney U test), variance ( F ), and regression ( B ) analyses. The results of the study show that the professional self-determination of adolescents increases their self-assessment of adulthood. The professional self-determination of adolescents is associated with the factor of primary professional socialization, namely, the conditions of the educational environment in which they grow up. The value orientations of adolescents are predictors of their self-assessment of adulthood, and are mediated by group, gender, and social stereotypes in the image of an adult and the role of an adult.